The Coralation Between Sanitation Facilities and Personal Hygiene with the Cases of Diarrhea in Breastfeeding Toddlers in Sinabung Post-Eruption Settlements, Berastagi District, Karo Regency - Irwansyah Lubis; Sri Malem Indirawati; Irnawati Marsaulina (Randwick International of Social Science Journal, 2021)
The purpose of this study was to analyze the relationship between basic sanitation facilities and personal hygiene with the incidence of diarrhea in breastfeeding infants in Sinabung post-eruption settlement, Berastagi District, Karo Regency in 2021. This study was a quantitative study with a Cross Sectional Study design. Data analysis using chi-square test with a sample of 100 mothers who have toddlers aged 6-24 months. The results showed that the related variables were basic sanitation facilities (p=0.014) and hand hygiene (p=0.020) with the incidence of diarrhea in breastfeeding infants. Suggestions for this study to health workers are expected to carry out health promotion and education about basic sanitation and personal hygiene to mothers whose toddlers do not experience diarrhea to prevent an increase in cases of diarrhea and to provide treatment and education to mothers whose toddlers experience diarrhea so as not to occurrence of complications or severity of diarrhea to prevent death.